ТHE TYPE, THE PURPOSE (GOAL) AND THE WAYS OF REDUCING THE SHARE CAPITAL OF THE LIMITED LIABILITY COMPANY - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Decrease in share capital is a procedure established by law, the successful implementation of which results in a decrease in value up to then registered share capital. The subject matter of this paper is one of the most important issues related to the process of reducing the share capital: the type, the purpose (goal) and the ways of reducing the share capital of the limited liability company. Although the Companies Act of Republic of Serbia does not mention the type of reduction in the share capital, in economic and legal theory, but also comparative law, the type of the decrease in the share capital was made according to two criteria. According to the economic criterion, as well as in the increase in the share capital, the effective and nominal decrease in the share capital is different. This economic classification has led to the creation of two different legal procedures for reducing the share capital in the law of companies. In this regard, the regular and the simplified procedure for the reduction of the share capital differ. The goal or more of them are the reasons why the reduction in share capital is being implemented. The purpose (goal) of reducing the share capital is, on the one hand, the notification to the creditors of the company and, on the other hand, the protection of members of the limited liability company. Until the recent amendments to the Serbian Companies Act on the reduction of the share capital of a limited liability company, provisions on the reduction of the share capital of the joint stock company were applied accordingly. Therefore, there was no special regulation that would apply to the reduction of the core capital of a limited liability company. The new regulation, however, is incomplete. Such incomplete regulation of this procedure will probably cause even greater problems in practice.